2010
DOI: 10.1136/ip.2010.029215.273
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors contributing to road traffic crashes in a fast developing country: the neglected health problem

Abstract: AimThe main objective of this study was to explore the patterns of road traffi c crashes (RTCs) among drivers in Qatar and examine the contributing factors involved with road traffi c crashes. Design This is a cross sectional survey. Methods The study based on 1228 drivers. Face to face interview was conducted by well-trained research assistants based on a questionnaire covering socio-demographic information, driving history, type of vehicle, driver behaviour, details of crashes and accident pattern. Results T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 0 publications
4
27
2
2
Order By: Relevance
“…[6,7] Traffic collisions are the leading causes of morbidity and mortality worldwide, and a review of the literature revealed that 20% of deaths due to traffic collisions are sourced from trauma-related cardiac injuries. [8,9] In this regard, determining cardiac involvement in traffic collision cases is of high importance to tackle multiple trauma cases and decrease the number of deaths.…”
Section: Discussionmentioning
confidence: 99%
“…[6,7] Traffic collisions are the leading causes of morbidity and mortality worldwide, and a review of the literature revealed that 20% of deaths due to traffic collisions are sourced from trauma-related cardiac injuries. [8,9] In this regard, determining cardiac involvement in traffic collision cases is of high importance to tackle multiple trauma cases and decrease the number of deaths.…”
Section: Discussionmentioning
confidence: 99%
“…[4] In the literature, risk factors for and causes of temporal bone fractures are: younger age, male gender and motor vehicle accidents. [5][6][7][8] Similarly, in our series, traffic accidents were the primary mechanism of the injury, with a 54.5% ratio; 76.6% of the cases were male and the mean age was 34.1 years. This result may be related to the fact that young males are greater participants in traffic and industrial business.…”
Section: Discussionmentioning
confidence: 59%
“…Otolaringolojik bulgular sıklık sırası ile erken dönem iletim tipi işitme kaybı (%65, 8), kanlı otore (%61,2), hemotimpanum (%58,5), timpanik membran perforasyonu (%25,6), fasiyal sinir paralizisi (%12,3), serebrospinal otore (%8,5) ve sensörinöral işitme kaybı (%5,4) idi. Kırıkların çoğu petroz (%65,8) ve uzunlamasına tip (%51,2) idi.…”
Section: Bulgularunclassified
“…Few accidents are due purely to chance; but many are preventable through information, education and measures like improved planning and design of the environment. As road accidents account for about two-thirds of the overall accident mortality in Qatar [24][25][26][27] and the number of cars has also increased substantially during the last 15 years [28], it seems reasonable to suggest that programmes to prevent fatal motor vehicle accidents should be given priority in economic planning [25][26]. Preventive actions should be aimed, specifically the introduction of safety elements (seat belts.…”
Section: Resultsmentioning
confidence: 99%
“…Preventive actions should be aimed, specifically the introduction of safety elements (seat belts. helmets, child seats) and action on alcohol abuse, mobile phone use while driving which are a significant contributory factor to road accidents, should be enhanced [25][26][27]. These preventive actions are quoted among the main goals of many Developed and Developing National Health Plans [29].…”
Section: Resultsmentioning
confidence: 99%